The Living Nature with a Bridle an Essay on Monkeys in the Circuses in Vienna in the 19th Century - Wąsik, Monika (Not just the Clown and the Tiger. Sketches about Circus Arts, 2019)
This article presents the history of performances of trained monkeys in circuses and theaters of Vienna in the nineteenth century. In the 30s in the nineteenth century the monkey shows were in fact one of the greatest attractions of the Vienna circus, which amused not only the audience eager for simple entertainment, but also theater reviewers. Monkeys’ performances – especially when they appeared in costumes and imitated human behavior – aroused no less interest than shows with animals of prey. The popularity of this pastime in Vienna may be proved by the fact that the Prater formed only theaters that specialized in taming these animals. A trained monkey was once even a heroine of one of the plays by Johann Nestroy and in 1836 it appeared on stage in the famous Theater an der Wien.